PILLARS OF THE AUDIT ACTIVITY: MATERIALITY AND AUDIT RISK - ANA MARIA JOLDOŞ; IONELA CORNELIA STANCIU; GABRIELA GREJDAN (Annals of the University of Petrosani: Economics)
The purpose of this article is to present the issues of materiality andaudit risk within the activity of financial audit. The concepts of materiality and audit risk aredescribed from a theoretical perspective, providing approaches found within the national andinternational literature and within the specific legislation. A case study on the calculation ofmateriality and audit risk for an entity is presented in the last part of the article. Through thetheoretical approach and the case study, it was concluded that materiality has an importantrole in determining the type of report to be issued, that is why it can be considered helpful forthose involved in the audit process.